Hydration effects on DNA double helix stability modulates ligand binding to natural DNA in response to changes in water activity. - Ruggiero Neto, J. [UNESP]; Pereira de Souza, F. [UNESP]; Colombo, M. F. [UNESP] (My University, 2001)
In this work we present evidence that water molecules are actively involved on the control of binding affinity and binding site discrimination of a drug to natural DNA. In a previous study, the effect of water activity (a(w)) on the energetic parameters of actinomycin-D intercalation to natural DNA was determined using the osmotic stress method (39). This earlier study has shown evidence that water molecules act as an allosteric regulator of ligand binding to DNA via the effect of water activity on the long-range stability of the DNA secondary structure. In this work we have carried out DNA circularization experiments using the plasmid pUC18 in the absence of drugs and in the presence of different neutral solutes to evaluate the contribution of water activity to the energetics of DNA helix unwinding. The contribution of water to these independent reactions were made explicit by the description of how the changes in the free energy of ligand binding to DNA and in the free energy associated with DNA helix torsional deformation are linked to a(w) via changes in structural hydration. Taken together, the results of these studies reveal an extensive linkage between ligand binding affinity and site binding discrimination, and long range helix conformational changes and DNA hydration. This is strong evidence that water molecules work as a classical allosteric regulator of ligand binding to the DNA via its contribution to the stability of the double helix secondary structure, suggesting a possible mechanism by which the biochemical machinery of DNA processing takes advantage of the low activity of water into the cellular milieu.